Disability Inclusion in Latin America and the Caribbean : A Path To Sustainable Development - Garcia Mora, Maria Elena; Schwartz Orellana, Steven; Freire, German (World Bank, Washington, DC, 2021)
About 85 million persons with disabilities live in Latin America and the Caribbean today. They comprise a highly heterogeneous population, but share a common history of invisibility and exclusion. In the last decades, persons with disabilities have improved their situation in terms of statistical visibility, poverty reduction, access to schools, and increased recognition and participation in public and private spaces. Yet, they are more likely to live in households that are poor, are overrepresented amongst the vulnerable, continue to face unequal opportunities in the labor market, have lower accumulation of human capital, and have limited voice and agency to have their aspirations of development included in decision making. The report offers a snapshot of the drivers behind the persistent exclusion of persons with disabilities and proposes a framework to build an actionable agenda building on promising practices available in the region. The COVID-19 pandemic has laid bare the urgent need to build more inclusive and resilient societies. The region has shown its resilience in recovering from many crises in the past. Today, we are at a crucial flection point where it is clear that universal policies and economic growth alone are insufficient to eradicate the remaining pockets of exclusion. A disability-inclusive recovery should be at the core of the region’s rebuilding strategy. This matters in its own right but is also of utmost importance for the sustainability of the region.